The Influence of Price and Product Quality on Cosmetic Purchasing Decisions in a Marketplace - Desi Lestari; Dudung Juhana (LPPM STMIK Mardira Indonesia, 2024)
This study aims to examine the impact of price and product quality on consumer choices while purchasing cosmetics in a particular market. The research methodology entails conducting an online survey targeting 100 active users of a marketplace company who have purchased beauty products. The findings indicate that the combination of price and product quality substantially influences purchase choices, accounting for a total contribution of 87.4%. These data suggest that these elements are significant contributors to acquiring cosmetics online. The research suggests that Maybelline's management should prioritize the value dimensions of price and product quality in their marketing tactics. They should focus on techniques that uphold or improve product quality while ensuring competitive prices. This result offers valuable insights for cosmetic companies in navigating the growing competition in the e-commerce market.